The impact of maternal periodontitis in the development of asthma in the offspring. (21st April 2021) - Rodrigues, Grazielle; Wuo, Alexandre do Valle; Klein, Simone; de Almeida, Patrícia; Damazo, Amilcar Sabino; Marcos, Rodrigo Labat; Horliana, Anna Carolina Ratto Tempestini; Lino-dos-Santos-Franco, Adriana
Abstract: Clinical and experimental studies show an association between maternal periodontitis and adverse outcomes during gestation. On the other hand, there were no studies evaluating the impact of maternal periodontitis on the offspring. Thus, our objective was to investigate the repercussion of maternal periodontitis on the development of asthma in the offspring. Pregnant rats were submitted or not to periodontitis by ligature technique. Thirty days after birth, the puppies were sensitized and challenged with ovalbumin (OVA) in order to induce asthmatic response. Our results showed that maternal periodontitis reduced cellular infiltrate in the parenchyma of offspring, tracheal responsiveness, lung edema, and anti-OVA antibodies, without alter mucus as well as cytokines production. We concluded that periodontitis has relevant impact on the offspring's immune system, blunting the response to allergic and inflammatory stimulus. This study shows the important role of oral health during pregnancy and opens possibilities for future studies in order to explain the effects of periodontitis during pregnancy in the offspring.